Extended Release of Bupivacaine from Temperature-Responsive PNDJ Hydrogels Improves Postoperative Weight-Bearing in Rabbits Following Knee Surgery - Derek J. Overstreet; Gabriel Zdrale; Alex C. McLaren (MDPI AG, 2024)
Effective treatment of postoperative pain lasting for multiple days without opioids is an important clinical need. We previously reported analgesia lasting up to 96 h in a porcine soft tissue model of postoperative pain using SBG004, an extended-release formulation of bupivacaine based on the temperature-responsive polymer poly(N-isopropylacrylamide-co-dimethylbutyrolactone acrylamide-co-Jeffamine M-1000 acrylamide) [PNDJ]. Orthopaedic surgical sites such as the knee can involve complex sensory innervation which presents a distinct challenge to local anesthetic delivery. The purpose of this work was to evaluate the pharmacokinetics and efficacy of SBG004 in an orthopaedic surgical model in comparison to currently available local anesthetics. Pharmacokinetics following periarticular (PA) or intraarticular (IA) injection of SBG004 were compared against liposomal bupivacaine (Lip-Bupi) PA in New Zealand White rabbits (all doses 14.5 mg/kg). Analgesic efficacy of SBG004 (IA, PA, or IA + PA), three active comparators, and saline was evaluated following knee surgery in New Zealand White rabbits. Analgesia was assessed via weight-bearing on the operated limb during spontaneous large steps in video recordings. Systemic bupivacaine exposure lasted at least 7 days for SBG004 PA, 4 days for SBG004 IA, and 2 days for Lip-Bupi PA. In the analgesia study, weight-bearing in all active groups except SBG004 IA was more frequent versus saline through 8 h postoperatively (p < 0.05). Only SBG004 IA + PA resulted in a higher proportion of weight-bearing rabbits at 24 h versus saline (6/7 versus 2/10, p = 0.015). Analysis of pooled data from 24-72 h showed significantly greater frequency of weight-bearing in rabbits receiving SBG004 IA + PA (71%) versus saline (37%), ropivacaine cocktail (41%), and Lip-Bupi PA (36%). The results indicate that the release profile from SBG004 PA or IA coincides reasonably with the time course of postoperative pain, and SBG004 may produce longer duration of analgesia than local anesthetics currently used in knee surgery, including during the period of 24-72 h recognized as a target for extended-release local anesthetics.